Survey of 5 mm small‐field output factor measurements in Australia. (25th January 2018) - Oliver, Christopher P.; Butler, Duncan J.; Takau, Viliami; Williams, Ivan
Abstract: The Australian Radiation Protection and Nuclear Safety Agency (ARPANSA) held a comparison exercise in April 2016 where participants came to ARPANSA and measured the output factor of a nominal 5 mm cone attached to the ARPANSA Elekta Synergy (Elekta, Crawley, UK) linear accelerator. The goal of the exercise was to compare the consistency and methods used by independent medical physicists in measuring small‐field output factors. ARPANSA provided a three‐dimensional scanning tank for detector setup and positioning, but the participants were required to measure the output factor with their own detectors. No information regarding output factors previously measured was supplied to participants to make each result as independent as possible. Fifteen groups travelled to ARPANSA bringing a wide range of detectors and methods. A total of 30 measurements of the output factor were made. The standard deviation of the measurements (excluding one expected outlier from an uncorrected ionization chamber measurement) was 3.6%. The results provide an insight into the consistency of small‐field dosimetry being performed in Australia and New Zealand at the present time.